Tribocorrosive performance of grinding ball materials in Miller wear tests under sand and Cu ore slurries - Santos, J. M.A.; Pinto, L. M. [UNESP]; Mion, F. S.; Campideli, V. C.; Olegário, F. C.F.; Pinto, M. A.; Penagos, J. J.; Viáfara, C. C. (Elsevier, 2025)
Wear is the main cause of the high costs associated with the deterioration of grinding balls in a Cu ore processing plant. Recently, we confirmed a reduction in mill ball consumption by replacing low alloy steel with high chromium white cast iron (WCI) as the ball material. In order to provide a simple laboratory test to assist in the selection of more cost-effective materials, Miller wear tests were carried out to evaluate the tribocorrosive wear of commercial ball materials. The effect of slurry pH on the tribological performance under abrasion-corrosion conditions was also analyzed. Two commercial WCI were used as testing materials to study tribocorrosive wear under different conditions of slurry pH and abrasives (sand and Cu ore). WCI materials showed small differences in terms of chemical composition and hardness. However, 16Cr-2.9C had a coarser microstructure and a higher abrasion resistance, while 18Cr-2.0C exhibited a higher Cr:C ratio, resulting in superior corrosion resistance. Miller wear tests confirmed the superior tribocorrosive behavior of WCI compared to low alloy steel. The tribocorrosive behavior of WCI materials was primarily influenced by the alkalinity of the abrasive slurries. In slightly alkaline slurries, wear rates of both WCI materials were affected by their abrasion and corrosion resistance, as well as the greater abrasiveness of Cu ore compared to sand. Under highly alkaline slurry conditions, where the corrosion component of the synergistic effect was effectively inhibited, the most abrasion-resistant material (16Cr-3.0C) exhibited the best tribocorrosive performance in both sand and Cu ore slurries.
Keywords: Cu ore; Grinding balls; Miller wear test; Tribocorrosive wear